La réforme du Code criminel canadien en matière de troubles mentaux et son impact sur la détention des justiciables - Laberge, Danielle; Morin, Daphné; Robert, Marie (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1995)
This article discusses how pre-trial detention has become an important instrument in the treatment of the accused whose mental state has been questioned during the judicial process. This study is part of a major research trend centered on the hypothesis of criminalization of the mental illness. This hypothesis has been defined as a shift of groups of the population from the mental health system to the criminal justice system. First, the authors examine how the Criminal Code's dispositions and those regarding mental disorder, which have been revised in February 1992, can be associated with the Court's decisions regarding the release of the accused during the legal process. Then, the authors continue to look into the question concerning the articulation of dual decisional logic (judicial and psychiatric) by studying approximately 1 000 cases heard before the Criminal and Penal Chamber of the Québec Court in Montréal in 1992-1993, in which the mental illness issue was raised. This analysis will try to demonstrate a link between pre-trial detention and mental health problems. It will also show that, despite the adoption of the principle of presumption against custody during assessment orders regarding mental disorder, the Court practices are changing slowly and the new dispositions are rarely used.